1987
DOI: 10.1136/jnnp.50.6.752
|View full text |Cite
|
Sign up to set email alerts
|

Dominantly inherited Alzheimer's disease: cerebral glucose metabolism.

Abstract: SUMMARY Cerebral glucose metabolic rate (CMRGlu), measured by positron emission tomography, was bilaterally and symmetrically reduced in two patients with autosomal dominant Alzheimer's disease. Supramarginal gyri and temporal lobes were most severely affected. An isolated reduction of CMRGlu in the left supramarginal gyrus was observed in one asymptomatic at-risk subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…In agreement with CBF findings, positron emission tomography studies have revealed that reduced regional metabolic rates of glucose in the mesial temporal lobe structures is present in early AD, and correlates with the severity of dementia [84,[87][88][89]. In advanced AD cases, metabolic disturbances also affect the prefrontal and parietal association areas [93].…”
Section: Differential Diagnosis Of Ad and Vad: The Contribution Of Nementioning
confidence: 50%
“…In agreement with CBF findings, positron emission tomography studies have revealed that reduced regional metabolic rates of glucose in the mesial temporal lobe structures is present in early AD, and correlates with the severity of dementia [84,[87][88][89]. In advanced AD cases, metabolic disturbances also affect the prefrontal and parietal association areas [93].…”
Section: Differential Diagnosis Of Ad and Vad: The Contribution Of Nementioning
confidence: 50%
“…ADAD and sAD are both associated with elevated cortical PiB uptake, especially in the in the precuneus/posterior cingulate and prefrontal cortex (54)(55)(56). Reductions in glucose metabolism in the temporal and parietal lobes have also been observed in both diseases (57)(58)(59)(60). Finally, both LOAD and ADAD have been shown to result in cortical (51,(61)(62)(63)(64)(65) and hippocampal (63,(65)(66)(67)(68) atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…A severely decreased rate of carbohydrate catabolism is now well established either in the DAT brain [22][23][24] or in fibroblasts from Alzheimer patients [25]. In addition, multiple studies have shown drastic reductions in the DAT brain of several enzymes acting in glycolytic glucose breakdown, such as phosphofructokinase and hexokinase: phosphofructokinase was found to be decreased to 10 [26] and 60% [27] of control values, and hexokinase activity was diminished by 34% compared with normal controls [28].…”
Section: Discussionmentioning
confidence: 99%